If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2 = -23 + 9x Reorder the terms: 2 + 4x = -23 + 9x Solving 2 + 4x = -23 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 2 + 4x + -9x = -23 + 9x + -9x Combine like terms: 4x + -9x = -5x 2 + -5x = -23 + 9x + -9x Combine like terms: 9x + -9x = 0 2 + -5x = -23 + 0 2 + -5x = -23 Add '-2' to each side of the equation. 2 + -2 + -5x = -23 + -2 Combine like terms: 2 + -2 = 0 0 + -5x = -23 + -2 -5x = -23 + -2 Combine like terms: -23 + -2 = -25 -5x = -25 Divide each side by '-5'. x = 5 Simplifying x = 5
| -2/-4-5/1 | | 5s^4-405=0 | | -7/-2-0/3 | | 0.8(3-11n)+1.4n= | | 5y*3=2y+12 | | 6x^3-72x=0 | | 6x^2+18x-6=0 | | (10x-3)+(14x-4)=8-(15-22x) | | -2/-4+5/1 | | 3(x^2-6x+5)=0 | | 8-.75c=5 | | 36+2x=30 | | 4-6a=9-5a | | 1/12+456 | | 1/2m=-6/7 | | 7s^4-567=0 | | -12r+-48=-10r+-30 | | (6-2x)+4=-5x-2 | | q/6=54 | | 9-(2-3y)=6+2y-(4+y) | | 54=5x+5 | | 3/5c=1/6 | | 64c-121c^3=0 | | h-133=62 | | 11=120 | | -5m-5+4m=4-m+1 | | 11z=55 | | -23a=2a-10-a | | 6x-2y=-4.5 | | 2(x-4)=4x-8 | | -5(x+6)= | | x^2-16x+9=49/4 |